Pengaruh Sistem Informasi Akuntansi Manajemen dan Sistem Pengendalian Internal Terhdap Kualitas Laporan Dana BOS dengan Komitemen Pimpinan sebagai Variabel Moderating (Studi Pada SLTA Kota Gunungsitoli - Polem, Ismayanti; Irfan, Irfan; sari, Eka Nurmala (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study is a study conducted to test and analyze the effect of management accounting information systems and internal control systems on the quality of BOS fund reports with leadership commitment as a moderating variable at Gunungsitoli High School, with an associative research approach, and data collection techniques by distributing questionnaires, the sample was 63 respondents and using path analysis techniques using the SEM PLS application.Based on the research results, it was concluded that the Management Accounting Information System has an effect on the Quality of the BOS Fund Report with a positive influence, this shows that if the management accounting information system is good, it will improve the quality of the BOS fund report, the Internal Control System has an effect on the Quality of the BOS Fund Report with a positive influence, this shows that if the internal control system is good, it will improve the quality of the BOS fund report, Leadership Commitment moderates the effect of the Management Accounting Information System on the Quality of the BOS Fund Report, and Leadership Commitment moderates the effect of the Internal Control System on the Quality of the BOS Fund Report